A pioneering health education strategy based on the PRECEDE-PROCEED model for women’s health challenges: a systematic review and logic framework - Khadijeh Khademi; Mohammad Hossein Kaveh (BMC Women's Health)
Abstract Purpose This review seeks to examine the effectiveness of PRECEDE-PROCEED model- based interventions on women’s behaviors, health, quality of life and determinants during health challenges as well as associations between their constructs. Additionally, it aims to propose a logical framework for enhancing women’s behaviors, health, quality of life and determinants during health challenges. Methods In April 2025, three databases- PubMed, Scopus, and Science Direct- were searched. The search included words in the Title, Abstract, and Keywords without any time limitations. The search was filtered by Clinical Trial or Randomized Clinical Trial for PubMed, Article for Scopus, and Research articles for Science Direct. Studies conducted among women that utilized an educational intervention based on the PRECEDE-PROCEED model, were written in full-text English, and used validated quantitative health questionnaires were included in the analysis. Descriptive, cross-sectional designs as well as qualitative, longitudinal, or non-original studies were excluded from the review. The risk of bias in the included interventional studies was assessed using the Revised Cochrane risk-of-bias tool for randomized trials (RoB 2) and the Risk Of Bias In Nonrandomized Studies - of Interventions (ROBINS-I tool) which were specifically adapted for these study designs. The main objective of the interventional studies was to investigate the effectiveness of PRECEDE-PROCEED model-based interventions on women’s behaviors, health, quality of life and determinants during health challenges. A review was conducted based on the AMSTAR checklist, PRISMA checklist and PRISMA flow diagram. Data extraction was performed with the consensus of two authors, and a narrative synthesis approach was chosen for data synthesis, following the guidelines provided by the Centre for Reviews and Dissemination (CRD). Results Seven interventional studies were included in the final analysis. Our findings revealed that all reviewed studies provided evidence of the effectiveness of a PRECEDE-PROCEED- based intervention for improving women’s behaviors, health, quality of life and determinants during health challenges. However, due to the absence of standardized measurement indicators to identify and compare the outcomes of various studies, there is a need to develop a conceptual framework that could enhance our understanding of women’s health challenges including childbirth, postpartum, menopause and genital infections. This framework aims to incorporate knowledge and positive attitudes towards healthy behaviors and health-related challenging conditions, as well as self-efficacy as important “predisposing factors.” It also considers social support and supportive policies as crucial “reinforcing factors.” Furthermore, it acknowledges resources, skills, services and their cost as necessary “enabling factors.” Lastly, it recognizes healthy behaviors and a favorable environment as “impacts,” alongside improved health and optimal quality of life as significant “outcomes” of these factors. Conclusions The proposed conceptual framework could define a PRECEDE-PROCEED-based intervention as an effective “health education strategy” for addressing the most significant health challenges facing women.